Adaption of some leguminous trees for agroforestry use in the north coast of Colombia - Sánchez O., Jaime Fernando; Moreno, Raúl Alberto (1992)
Erythrina berteroana, E. fusca, E. poeppigiana, Gliricidia sepium, Leucaena leucocephala, and Senna siamea were grown for 15 months at two lowland sites in Colombia, L. leucocephala performed poorly in contrast to G. Sepium and S. Siamea.